Analisis laporan pertanggungjawaban Badan Usaha Milik Desa Berdasarkan Peraturan Bupati Kabupaten Minahasa Utara Nomor 25 Tahun 2019 pada BUMDES Budo Kecamatan Wori Kabupaten Minahasa Utara - Lanipi, Alicya Apriska Daratista; Kindangen, Wulan D. (Riset Akuntansi dan Manajemen Pragmatis, 2025)
This study aims to analyze the implementation of accountability reporting by the Village-Owned Enterprise (BUMDes) Sinar Usaha in Budo Village, Wori Subdistrict, North Minahasa Regency, based on North Minahasa Regent Regulation Number 25 of 2019. The research is motivated by the importance of ensuring accountability and transparency in the governance of BUMDes as a key instrument for rural economic empowerment and public fund management. A qualitative descriptive approach was employed, utilizing in-depth interviews and document analysis. The findings reveal that although BUMDes Budo has followed the calendar year reporting period and held village deliberation forums, several discrepancies with regulatory provisions persist. These include the absence of report validation by supervisory and advisory boards and the non-attendance of the subdistrict head in accountability forums. Furthermore, the development report focuses solely on annual revenue figures without comprehensive written documentation or performance analysis. The results underscore the need for a more structured reporting mechanism, enhanced managerial capacity, and stronger coordination among stakeholders to ensure transparent, accountable, and sustainable BUMDes governance.